2011
DOI: 10.1007/s00296-011-1928-5
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue in patients with ankylosing spondylitis: prevalence and relationships with disease-specific variables, psychological status, and sleep disturbance

Abstract: This study aims to evaluate the frequency of fatigue in Moroccan patients with ankylosing spondylitis (AS), and its relationships with disease-specific variables, psychological status, and sleep disturbance. A cross-sectional study included patients fulfilled the modified New York classification criteria for ankylosing spondylitis. To assess fatigue, the first item of Bath ankylosing spondylitis disease activity index (BASDAI) and the multidimensional assessment of fatigue (MAF) was used. The evaluation includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
62
2
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(70 citation statements)
references
References 32 publications
2
62
2
1
Order By: Relevance
“…A recent study [20] showed that nonsteroidal antiinflammatory drug therapy strongly reduced pain and functional impairment in a group of AS patients, whereas the change in fatigue level was of lower magnitude. Similarly in other studies, we found no impact of nonsteroidal anti-inflammatory drugs [NSAID] and disease-modifying antirheumatic drugs [DMARD] on fatigue degree [14] [21]. In our study, laboratory measurements like ESR and CRP were no found to be related with fatigue.…”
Section: Discussioncontrasting
confidence: 31%
See 2 more Smart Citations
“…A recent study [20] showed that nonsteroidal antiinflammatory drug therapy strongly reduced pain and functional impairment in a group of AS patients, whereas the change in fatigue level was of lower magnitude. Similarly in other studies, we found no impact of nonsteroidal anti-inflammatory drugs [NSAID] and disease-modifying antirheumatic drugs [DMARD] on fatigue degree [14] [21]. In our study, laboratory measurements like ESR and CRP were no found to be related with fatigue.…”
Section: Discussioncontrasting
confidence: 31%
“…Only a few studies have been published examining determinants of fatigue in SpA, and all have focused on ankylosing spondylitis [AS] [14]. To our knowledge, there is no study which have been published examining determinants of fatigue in USpA.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Patient demographic characteristics and diseasespecific variables included scores on the Bath AS Disease Activity Index (BASDAI) (3,24) and the Bath AS Metrology Index (BASMI) (25), as well as the serum C-reactive protein levels and erythrocyte sedimentation rates, and total back pain scores on a scale of 0-10 (0 ϭ no pain, 10 ϭ most intense pain imaginable). Cognitive/affective functions were evaluated using the Pain Catastrophizing Scale (PCS; range 0-52) (26) and the 40-item, 6-point Affect Intensity Measure (AIM) to assess the characteristic affect strength (27).…”
Section: Methodsmentioning
confidence: 99%
“…Yet, it is undertreated. In ankylosing spondylitis (AS), fatigue is a frequent and significant symptom, reported in 50-70% of patients (3)(4)(5)(6), and it is associated with disease severity, functional ability, global well-being, and mental health status. Traditional approaches to the treatment of fatigue, such as exercise programs, have proven difficult to institute in AS patients (7).…”
mentioning
confidence: 99%